فعالية برنامج قائم على طريقة فيرنالد في خفض عسر القراءة (دراسة ميدانية على التلاميذ ذوي صعوبات التعليم بمجلس الأشخاص ذوي الإعاقة بمدينة بورتسودان، ولاية البحر الأحمر، السودان، 2025م) - يوسف علي, ماريا محمد; حاج الشيخ, هادية مبارك (Gezira Journal of Educational Sciences and Humanities; مجلد 20 عدد 1 (2023), 2026)
هدفت هذه الدراسة إلى قياس فاعلية طريقة فيرنالد - أحد التطبيقات العملية لأسلوب تعدد الحواس- في علاج عسر القراءة (الديسلكسيا) لدى التلاميذ المشخّصين بصعوبات التعلم في مجلس الأشخاص ذوي الإعاقة بمدينة بورتسودان، استخدمت الدراسة المنهج شبه التجريبي مستعينة بالتصميم التجريبي ذي المجموعتين الضابطة والتجريبية، وقد استخدمت الدراسة مقياس العسر القرائي من إعداد الباحثتين، كما استخدمت طريقة فيرنالد لتعدد الحواس. أداة للدراسة. تم اختيار عينة الدراسة بطريقة قصدية من مجلس الأشخاص ذوي الإعاقة بمدينة بورتسودان في ولاية البحر الأحمر شرقي جمهورية السودان، وقد تكونت العينة من (12) طالباً وطالبة، تم اختيارها بالطريقة العشوائية المنتظمة؛ وهي تمثل (26.7%) من مجتمع الدراسة (التلاميذ ذوي صعوبات التعلّم في المجلس) البالغ عددهم (45) تلميذاً وتلميذة، وتم تحليل بيانات الدراسة باستخدام طريقة الحزم الإحصائية للعلوم الاجتماعية .(SPSS) توصّلت الدراسة إلى النتائج التالية: لاستخدام طريقة فيرنالد  لتعدد الحواس فاعلية دالة إحصائياً في علاج العسر القرائي لدى أطفال صعوبات التعلّم في مجلس الأشخاص ذوي الإعاقة بمدينة بورتسودان بولاية البحر الأحمر(1. 72)، توجد فروق ذات دلالة إحصائية بين متوسطي رتب درجات عينة الدراسة في القياسين القبلي والبعدي على مقياس عسر القراءة، تُعزى إلى استخدام طريقة فيرنالد لتعدد الحواس لدى التلاميذ ذوي صعوبات التعلّم لصالح القياس البعدي (3. 051)، توجد فروق ذات دلالة إحصائية بين متوسطي درجات المجموعة التجريبية في التطبيق القبلي والبعدي على مقياس عسر القراءة، تُعزى إلى استخدام طريقة فيرنالد لتعدد الحواس لدى التلاميذ ذوي صعوبات التعلّم لصالح المجموعة التجريبية (0. 01)، لا توجد فروق ذات دلالة إحصائية بين متوسطات درجات المجموعة التجريبية على مقياس عسر القراءة بعد استخدام طريقة فيرنالد لتعدد الحواس لدى التلاميذ ذوي صعوبات التعلّم تُعزى إلى نوع التلميذ (ذكر- أنثى) (3. 907).  أوصت الدراسة بالاهتمام باختيار الطريقة المناسبة للعمر العقلي والزمني للأطفال ذوي اضطراب صعوبات التعلّم للتدريب عليه، بعد إجراء عملية التقييم الدقيقة لهم، حتى يُوفر ما لديهم من فرص ضائعة بسبب سوء اختيار البرامج المناسبة.  واقترحت الباحثتين إجراء دراسة حول فاعلية طريقة فيرنالد في تحسين المهارات الاجتماعية لدى الأطفال ذوي صعوبات التعلّم، والاضطراب النمائية الأخرى. This study aimed to measure the effectiveness of the Fernald program - one of the practical applications of the multisensory method - in treating dyslexia among students diagnosed with learning difficulties in the Council for Persons with Disabilities in Port Sudan. The study used the quasi-experimental approach using the experimental design with two groups: control and experimental. The study used the dyslexia scale prepared by the researcher, and the Fernald program for multisensory learning was used as study tools. The study sample was selected intentionally from the Council for Persons with Disabilities in Port Sudan in the Red Sea State, eastern Sudan. The sample consisted of (12) male and female students; It represents (26.7%) of the study population (students with learning difficulties in the council) numbering (45) male and female students. The study data were analyzed using the Statistical Package for Social Sciences (SPSS) program. The study reached the following results: The use of the Fernald program for multisensory learning was statistically significant in treating dyslexia among children with learning difficulties in the Council for Persons with Disabilities in Port Sudan, Red Sea State (1.72). There are statistically significant differences between the average ranks of the study sample’s scores in the pre- and post-measurements on the dyslexia scale, attributed to the use of the Fernald program for multisensory learning among students with learning difficulties in favor of the post-measurement (3.051). There are statistically significant differences between the average scores of the experimental group in the pre- and post-application on the dyslexia scale, attributed to the use of the Fernald program for multisensory learning among students with learning difficulties in favor of the experimental group (0.01). There are no statistically significant differences between the average scores of the experimental group on the dyslexia scale, after using Fernald's multisensory program for students with learning disabilities is attributed to the student's gender (male-female) (3.907). The study recommended that attention be paid to selecting a program appropriate for the mental and chronological age of children with learning disabilities to train on, after conducting a thorough evaluation process for them, in order to save them from lost opportunities due to poor selection of appropriate programs. It suggested conducting a study on the effectiveness of a proposed program in improving social skills in children with learning disabilities and other developmental disorders.